Exosomes Derived from Bone Marrow Stromal Cells (BMSCs) Enhance Tendon-Bone Healing by Regulating Macrophage Polarization - Shi, Youxing; Kang, Xia; Wang, Yunjiao; Bian, Xuting; He, Gang; Zhou, Mei; Tang, Kanglai (Medical science monitor, 2020)
BACKGROUND Inflammation after tendon-bone junction injury results in the formation of excessive scar tissue and poor biomechanical properties. Recent research has shown that exosomes derived from bone marrow stromal cells (BMSCs) can modulate inflammation during tissue healing. Thus, our study aimed to enhance tendon-bone healing by use of BMSC-derived exosomes (BMSC-Exos). MATERIAL AND METHODS The mouse tendon-bone reconstruction model was established, and the mice were randomly divided into 3 groups: the control group, the hydrogel group, and the hydrogel+exosome group, with 30 mice in each group. At 7 days, 14 days, and 1 month after surgery, tendon-bone junction samples were harvested, and the macrophage polarization and tendon-bone healing were evaluated based on histology, immunofluorescence, and quantitative RT-PCR (qRT-PCR) analysis. RESULTS In the early phase, we observed significantly higher numbers of M2 macrophages and more anti-inflammatory and chondrogenic-related factors in the hydrogel+BMSC-Exos group compared with the control group and the hydrogel group. The M1 macrophages and related proinflammatory factors decreased. Cell apoptosis decreased in the hydrogel+BMSC-Exos group, while cell proliferation increased; in particular, the CD146+ stem cells substantially increased. At 1 month after surgery, there was more fibrocartilage in the hydrogel+BMSC-Exos group than in the other groups. Biomechanical testing showed that the maximum force, strength, and elastic modulus were significantly improved in the hydrogel+BMSC-Exos group. CONCLUSIONS Our study provides evidence that the local administration of BMSC-Exos promotes the formation of fibrocartilage by increasing M2 macrophage polarization in tendon-to-bone healing, leading to improved biomechanical properties. These findings provide a basis for the potential clinical use of BMSC-Exos in tendon-bone repair.